Health disparities and treatment approaches in portopulmonary hypertension and idiopathic pulmonary arterial hypertension: an analysis of the Pulmonary Hypertension Association Registry - Hilary M. DuBrock; Charles D. Burger; Sonja D. Bartolome; Jeremy P. Feldman; D. Dunbar Ivy; Erika B. Rosenzweig; Jeffrey S. Sager; Kenneth W. Presberg; Stephen C. Mathai; Matthew R. Lammi; James R. Klinger; Michael Eggert; et al. (Pulmonary Circulation)
Compared to idiopathic pulmonary arterial hypertension (IPAH), patients with portopulmonary hypertension (POPH) have worse survival. Health disparities may contribute to these differences but have not been studied. We sought to compare socioeconomic factors in patients with POPH and IPAH and to determine whether socioeconomic status and/or POPH diagnosis were associated with treatment and health‐care utilization. We performed a cross‐sectional study of adults enrolled in the Pulmonary Hypertension Association Registry. Patients with IPAH (n = 344) and POPH (n = 57) were compared. Compared with IPAH, patients with POPH were less likely to be college graduates (19.6% vs. 34.9%, p = 0.02) and more likely to be unemployed (54.7% vs. 30.5%, p < 0.001) and have an annual household income below poverty level (45.7% vs. 19.0%, p < 0.001). Patients with POPH had similar functional class, quality of life, 6‐min walk distance, and mean pulmonary arterial pressure with a higher cardiac index. Compared with IPAH, patients with POPH were less likely to receive combination therapy (46.4% vs. 62.2%, p = 0.03) and endothelin receptor antagonists (28.6% vs. 55.1%, p < 0.001) at enrollment with similar treatment at follow‐up. Patients with POPH had more emergency department visits (1.7 ± 2.1 vs. 0.9 ± 1.2, p = 0.009) and hospitalizations in the six months preceding enrollment (1.5 ± 2.1 vs. 0.8 ± 1.1, p = 0.02). Both POPH diagnosis and lower education level were independently associated with a higher number of emergency department visits. Compared to IPAH, patients with POPH have lower socioeconomic status, are less likely to receive initial combination therapy and endothelin receptor antagonists but have similar treatment at follow‐up, and have increased health‐care utilization.